2018
DOI: 10.1053/j.gastro.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Indigo Naturalis in a Multicenter Randomized Controlled Trial of Patients With Ulcerative Colitis

Abstract: In a randomized, placebo-controlled trial, we found 8 weeks of IN (0.5-2.0 g per day) to be effective in inducing a clinical response in patients with UC. However, IN should not yet be used because of the potential for adverse effects, including pulmonary arterial hypertension. Clinical Trials Registry no: UMIN000021439 (http://www.umin.ac.jp/ctr/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
155
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 33 publications
4
155
1
1
Order By: Relevance
“…Although the therapeutic efficacy of IN remains debatable, a recent multicenter randomized, double-blind, placebo-controlled study demonstrated its favorable therapeutic effects in inducing remission in UC. 11 The present study also showed that IN demonstrates a good therapeutic effect in inducing remission in UC. In addition, we also found a good maintenance effect of IN in UC.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Although the therapeutic efficacy of IN remains debatable, a recent multicenter randomized, double-blind, placebo-controlled study demonstrated its favorable therapeutic effects in inducing remission in UC. 11 The present study also showed that IN demonstrates a good therapeutic effect in inducing remission in UC. In addition, we also found a good maintenance effect of IN in UC.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, approximately half of the patients with UC were treated using 2.0 g/day, while the other half took 3.0 g/day for induction therapy. A recent randomized clinical trial for UC demonstrated a significant dose‐dependent linear trend in the clinical response at week 8 (placebo, 13.6%; 0.5 g/day, 69.6%; 1.0 g/day, 75.0%; 2.0 g, 81.0%) . In the present study, the therapeutic efficacy in inducing remission was comparable between UC patients treated using 2.0 g/day and those treated using 3.0 g/day (data not shown), and higher rates of clinical remission at weeks 4 and 8 might be attributed to the fact that larger doses of IN were administered.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations